Pembelajaran Melalui Dongeng dan Permainan di TK Mawar Indah 01 Kota Batu - Maharani, Dian; Fauzi, Deri (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
KKM-DR is a compulsory course for every student in UIN Maulana Malik Ibrahim Malang who already passed at least 100 credits. This year, a team of KKM-DR students choose Sidomulyo Village to be their destination village. They were asked to teach in TK Mawar Indah 01. The learning methods they used are learning by games and fairy tales. By using this method, students learn to use their motoric, learn about color, geometric shapes, counting, reading, and learn about nature.